Identification of Substitutions and Small Insertion-Deletions Induced by Carbon-Ion Beam Irradiation in Arabidopsis thaliana - Du, Yan; Luo, Shanwei; Li, Xin; Yang, Jiangyan; Cui, Tao; Li, Wenjian; Yu, Lixia; Feng, Hui; Chen, Yuze; Mu, Jinhu; Chen, Xia; Shu, Qingyao; et al. (Frontiers in Plant Science, 2017)
Heavy-ion beam irradiation is one of the principal methods used to create mutants in plants. Research on mutagenic effects and molecular mechanisms of radiation is an important subject that is multi-disciplinary. Here, we re-sequenced 11 mutagenesis progeny (M3) Arabidopsis thaliana lines derived from carbon-ion beam (CIB) irradiation, and subsequently focused on substitutions and small insertion-deletion (INDELs). We found that the CIB induced more substitutions (320) than INDELs (124). Meanwhile, the single base INDELs were more prevalent than those in large size (≥ 2 bp). In details, the detected substitutions showed an obvious bias of C > T transitions, by activating the formation of covalent linkages between neighboring pyrimidine residues in the DNA sequence. An A and T bias was observed among the single base INDELs, in which most of these were induced by replication slippage at either the homopolymer or polynucleotide repeat regions. The mutation rate of 200-Gy CIB irradiation was estimated as 3.37 × 10-7 per site. Different from previous researches which mainly focused on the phenotype, chromosome aberration, genetic polymorphism, or sequencing analysis of specific genes only, our study revealed genome-wide molecular profile and rate of mutations induced by CIB irradiation. We hope our data could provide valuable clues for explaining the potential mechanism of plant mutation breeding by CIB irradiation.